Passions, Politics and the Limits of Society - Stapelbroek, Koen / Haara (Helsinki Yearbook of Intellectual History, 2020)
The 1st part of the volume engages with the theme of inclusion and exclusion in the history of ideas from different perspectives. The 2nd part of the volume discusses debates on natural law, human nature and political economy in early-modern Europe. Its contributions explore the sorts of political and moral visions that were relevant in post-Hobbesian moral philosophy and the development of economic thought.